Can all bulk-phase reactions be accelerated in microdroplets?. Issue 9 (23rd March 2017) - Banerjee, Shibdas; Gnanamani, Elumalai; Yan, Xin; Zare, Richard N.
Abstract : In contrast to bulk-phase reactions, microdroplet reactions can alter the kinetics or reaction route by its surface activity. Abstract : Recent studies have shown that microdroplet reactions are markedly accelerated compared to the corresponding bulk-phase reactions. This raises the question whether all reactions can be sped up by this means. We present a counter example, and we show that the reaction mechanism in microdroplets can differ sharply from that in bulk, especially because of the distinct microdroplet surface environment. This analysis helps to guide us how to choose and control reactions in microdroplets and provides a possible perspective on utilizing microdroplet chemistry to scale up synthesis.